Contractual Freedom and Compulsory Insurance: An Imperative Compromise? A Comparative Study in Quebec and French Law - Part One - Hadid, Jason (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2005)
This comparative paper analyses the disparity between Quebec and French Law with respect to compulsory insurance and highlights the importance attached to the principle of contractual freedom in Quebec. The steadfast development and protection of this principle in Quebec may be attributed to the influence of North-American capitalism and long-standing principles of both the Anglo-Saxon and Napoleonic legal traditions while, in France, an ever-growing trend towards the collective protection of the public has overshadowed any individual right to contractual freedom with respect to many activities. With 119 compulsory insurance stipulations forming an integral chapter of the French Code des assurances, one begins to wonder whether Insurance Law in Quebec will follow suit. Could this ever occur? Should it? The legal repercussions of such a development (such as the correlative obligation to insure necessarily imposed on private insurance companies) are examined, as well as the current state of Quebec and French Law pertaining to compulsory insurance and contractual freedom. This Part One of a two-part series deals entirely with French Law. Part Two, which deals with Quebec Law, will be published in the April 2006 issue.